Carbon‐Supported High‐Entropy Oxide Nanoparticles as Stable Electrocatalysts for Oxygen Reduction Reactions - Li, Tangyuan; Yao, Yonggang; Ko, Byung Hee; Huang, Zhennan; Dong, Qi; Gao, Jinlong; Chen, Wilson; Li, Jianguo; Li, Shuke; Wang, Xizheng; Shahbazian‐Yassar, Reza; Jiao, Feng; et al. (Advanced functional materials, 2021)
Nanoparticles supported on carbonaceous substrates are promising electrocatalysts. However, achieving good stability for the electrocatalysts during long‐term operations while maintaining high activity remains a grand challenge. Herein, a highly stable and active electrocatalyst featuring high‐entropy oxide (HEO) nanoparticles uniformly dispersed on commercial carbon black is reported, which is synthesized via rapid high‐temperature heating (≈1 s, 1400 K). Notably, the HEO nanoparticles with a record‐high entropy are composed of ten metal elements (i.e., Hf, Zr, La, V, Ce, Ti, Nd, Gd, Y, and Pd). The rapid high‐temperature synthesis can tailor structural stability and avoid nanoparticle detachment or agglomeration. Meanwhile, the high‐entropy design can enhance chemical stability to prevent elemental segregation. Using oxygen reduction reaction as a model, the 10‐element HEO exhibits good activity and greatly enhances stability (i.e., 92% and 86% retention after 12 and 100 h, respectively) compared to the commercial Pd/C electrocatalyst (i.e., 76% retention after 12 h). This superior performance is attributed to the high‐entropy compositional design and synthetic approach, which offers an entropy stabilization effect and strong interfacial bonding between the nanoparticles and carbon substrate. The approach promises a viable route toward synthesizing carbon‐supported high‐entropy electrocatalysts with good stability and high activity for various applications. The long‐term durability of electrocatalysts remains a major challenge due to issues such as nanoparticle detachment, agglomeration, and elemental segregation. This study demonstrates a series of carbon‐supported high‐entropy oxide (HEO/C) nanoparticles for stable electrocatalysts. In particular, a 10‐element HEO/C shows superior stability in the oxygen reduction reaction compared to the commercial Pd/C electrocatalyst.